Poéticas do vestígio: fait, as terras do fim do mundo e to face - Kátia Hallak Lombardi (2015)
This study examines the specific characteristics present in the works of three photographers, each of whom includes traces of war as their central theme: Sophie Ristelhuebers Fait (1992), Jo Ractliffes As terras do fim do mundo (2010), and Paola De Pietris To face (2012). It first addresses the process of the construction of war photography. Subsequently, the dissertation elaborates upon photographic works that broach the subject of war without, however, showing images of combat or action itself. Further, the research returns to the notion of indicial photography and turns to Walter Benjamins writings and his readers in order to reflect upon the concept of trace. Using this theoretical paradigm, the dissertation analyzes the unique methods each of the three photographers Ristelhueber, Ractliffe and De Pietri employs in working with the traces of war in their photography, and suggests that their work functions as a poetics of trace.